2023
DOI: 10.3389/fmed.2023.1107967
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of tetrandrine in artificial stone-associated silicosis: A retrospective cohort study

Abstract: BackgroundOutbreaks of silicosis have occurred among workers in the artificial stone (AS) industry, and there is currently no effective antifibrosis treatment for silicosis.DesignA retrospective cohort study.MethodsWe retrospectively analyzed the clinical data of 89 artificial stone-associated silicosis patients treated in Shanghai Pulmonary Hospital (China). Patients who agreed to be administered tetrandrine entered the observation group and those who disagreed entered the control group. Changes in chest HRCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…From the results of this study, we found that Tet has great potential to slow the progression of PMF fibrosis as well as the aggravation of emphysema. Similar to the results of a recent study, which showed that after taking Tet for 3–12 months, 56.5 to 65.4% of silicosis patients had improved HRCT [ 9 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…From the results of this study, we found that Tet has great potential to slow the progression of PMF fibrosis as well as the aggravation of emphysema. Similar to the results of a recent study, which showed that after taking Tet for 3–12 months, 56.5 to 65.4% of silicosis patients had improved HRCT [ 9 ].…”
Section: Discussionsupporting
confidence: 89%
“…Tetrandrine (Tet) as a potent calcium channel blocker and in the treatment of different health issues has been referenced in Chinese Pharmacopoeia for its use as an anti-silicosis agent [ 7 ]. Previous studies have reported that silicotic nodules under X-ray have reduced and lung function have improved after Tet treatment [ 8 , 9 ]. However, the effect of Tet on PMF has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies have found that Tet can control and postpone the pathological process of pulmonary fibrosis in silicosis patients (chest HRCT imaging evidence, lung function, changes of molecular indexes related to lung inflammation and fibrosis, etc.) [ 26 , 27 , 29 ]. In this study, the results of histopathological experiments showed that Tet intervention could significantly alleviate lung inflammation and fibrosis in mice caused by SiO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly used to treat arthritis, hypertension, tumors, silicosis, liver fibrosis prevention and treatment, liver cell protection, and other conditions in clinical practice [ 23 , 24 , 25 ]. Both in vitro and in vivo studies have confirmed that Tet is effective in the treatment of silicosis [ 26 , 27 , 28 , 29 ]. Currently, tetrandrine (Tet) is the only plant-derived drug approved in China for the treatment of silicosis.…”
Section: Introductionmentioning
confidence: 99%
“…The Chinese medicinal vine plant Stephania tetranda S. Moore contains a bisbenzylisoquinoline alkaloid named tetrandrine. Recent clinical studies have reported improved outcomes in patients with COVID-19 and those with silicosis when treated with tetrandrine [153,154]. Aside from its calcium-channel-blocking properties, accumulating evidence suggests that it targets cancer-associated inflammation, induces apoptosis, and reverses multidrug-resistant cancer cell lines [155].…”
Section: Alkaloidsmentioning
confidence: 99%